Understanding What is Esoteric. - Blake, Anthony (Correspondences, 2020)
Intrinsic to the teachings of G. I. Gurdjieff is the notion of the esoteric—his Fourth Way forms an essential part of the current of Western esotericism, and his teachings affirm the fundamental aspects of philosophia perennis, the concept of a universal, timeless, but hidden wisdom only accessible to an elite few. This study examines how the attendant notions of knowledge, learning, reading, and transmission operate in Gurdjieff’s work, and embeds these motifs in a broader context of the esoteric literature of both historical religions and the modern era. It demonstrates that Gurdjieff is both the revealer of knowledge and the cause of its obfuscation, requiring seekers to undergo various methods of exertion and personal transformation in order to become recipients of gnosis. Thus, the search for esoteric knowledge, as well as the knowledge itself, is presented as a path of danger and strife but also great reward.